Evidence for GABA‐A receptor dysregulation in gambling disorder: correlation with impulsivity. (13th October 2016) - Mick, Inge; Ramos, Anna C.; Myers, Jim; Stokes, Paul R.; Chandrasekera, Samantha; Erritzoe, David; Mendez, Maria A.; Gunn, Roger N.; Rabiner, Eugenii A.; Searle, Graham E.; Galduróz, José C. F.; Waldman, Adam D.; et al.
Abstract: As a behavioural addiction, gambling disorder (GD) provides an opportunity to characterize addictive processes without the potentially confounding effects of chronic excessive drug and alcohol exposure. Impulsivity is an established precursor to such addictive behaviours, and GD is associated with greater impulsivity. There is also evidence of GABAergic dysregulation in substance addiction and in impulsivity. This study therefore investigated GABAA receptor availability in 15 individuals with GD and 19 healthy volunteers (HV) using [ 11 C]Ro15‐4513, a relatively selective α5 benzodiazepine receptor PET tracer and its relationship with impulsivity. We found significantly higher [ 11 C]Ro15‐4513 total distribution volume ( VT ) in the right hippocampus in the GD group compared with HV. We found higher levels of the 'Negative Urgency' construct of impulsivity in GD, and these were positively associated with higher [ 11 C]Ro15‐4513 VT in the amygdala in the GD group; no such significant correlations were evident in the HV group. These results contrast with reduced binding of GABAergic PET ligands described previously in alcohol and opiate addiction and add to growing evidence for distinctions in the neuropharmacology between substance and behavioural addictions. These results provide the first characterization of GABAA receptors in GD with [ 11 C]Ro15‐4513 PET and show greater α5 receptor availability and positive correlations with trait impulsivity. This GABAergic dysregulation is potential target for treatment. Abstract : We used [ 11 C]Ro15–4513 PET to assess GABA‐a5 receptor availability in gambling disorder (GD) and impulsivity. We found significantly higher [ 11 C]Ro15–4513 total distribution volume (VT ) in the right hippocampus in GD compared with healthy volunteers. We found higher levels of The 'Negative Urgency' construct of impulsivity in GD that positively associated with higher [ 11 C]Ro15–4513 VT in the amygdala in the GD group; no such significant correlations were evident in the healthy volunteers group.